Early signs of recovery suggested by changes in the structure and function of deep-sea megabenthic communities on a seamount 19 years after fishing - Savannah L. Goode; Ashley A. Rowden; Malcolm R. Clark; David A. Bowden; Fabrice Stephenson (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Using joint species distribution modelling to predict distributions of seafloor taxa and identify vulnerable marine ecosystems in New Zealand waters - Fabrice Stephenson; David A. Bowden; Ashley A. Rowden; Owen F. Anderson; Malcolm R. Clark; Matthew Bennion; Brittany Finucci; Matt H. Pinkerton; Savannah Goode; Caroline Chin; Niki Davey; Alan Hart; et al. (Biodiversity and Conservation, 2024)
Effective ecosystem-based management of bottom-contacting fisheries requires understanding of how disturbances from fishing affect seafloor fauna over a wide range of spatial and temporal scales. Spatial predictions of abundance for 67 taxa were developed, using an extensive dataset of faunal abundances collected using a towed camera system and spatially explicit predictor variables including bottom-trawl fishing effort, using a Joint Species Distribution Model ( JSDM ). The model fit metrics varied by taxon: the mean tenfold cross-validated AUC score was 0.70 ± 0.1 (standard deviation) for presence–absence and an R 2 of 0.11 ± 0.1 (standard deviation) for abundance models. Spatial predictions of probability of occurrence and abundance (individuals per km 2 ) varied by taxon, but there were key areas of overlap, with highest predicted taxon richness in areas of the continental shelf break and slope. The resulting joint predictions represent significant advances on previous predictions because they are of abundance, allow the exploration of co-occurrence patterns and provide credible estimates of taxon richness (including for rare species that are often not included in more commonly used single-species distribution modelling). Habitat-forming taxa considered to be Vulnerable Marine Ecosystem (VME) indicators (those taxa that are physically or functionally fragile to anthropogenic impacts) were identified in the dataset. Spatial estimates of likely VME distribution (as well as associated estimates of uncertainty) were predicted for the study area. Identifying areas most likely to represent a VME (rather than simply VME indicator taxa) provides much needed quantitative estimates of vulnerable habitats, and facilitates an evidence-based approach to managing potential impacts of bottom-trawling.

Implications for the conservation of deep-water corals in the face of multiple stressors: A case study from the New Zealand region - Fabrice Stephenson; Ashley A. Rowden; Owen F. Anderson; Joanne I. Ellis; Shane W. Geange; Tom Brough; Erik Behrens; Judi E. Hewitt; Malcolm R. Clark; Dianne M. Tracey; Savannah L. Goode; Grady L. Petersen; et al. (Journal of Environmental Management, 2023)

Differences in Intentional Weight Loss Strategies According to Race/ethnicity Among US Women, NHANES 2007 – 2018 - A. Gutierrez; R. Goode; M. Slining; L. Butler (Journal of the Academy of Nutrition and Dietetics, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Fine-Scale Mapping of Mega-Epibenthic Communities and Their Patch Characteristics on Two New Zealand Seamounts - Savannah L. Goode; Ashley A. Rowden; David A. Bowden; Malcolm R. Clark; Fabrice Stephenson (Frontiers in Marine Science, 2021)
Seamounts are common features of the deep seafloor that are often associated with aggregations of mega-epibenthic fauna, including deep-sea corals and sponges. Globally, many seamounts also host abundant fish stocks, supporting commercial bottom trawl fisheries that impact non-target benthic species through damage and/or removal of these non-target species. However, the effects of bottom trawling on seamount benthic communities, as well as their recovery potential, will vary over the total seamount area because of differences in within seamount habitat and community structure. It is therefore important to understand fine-scale community dynamics, community patch characteristics, and the environmental drivers contributing to these patterns to improve habitat mapping efforts on seamounts and to determine the potential for benthic communities on seamounts to recover from fishing disturbances. Here we analysed the structure and distribution of mega-epibenthic communities on two New Zealand seamounts with different physical environments to determine which environmental variables best correlated with variation in community structure within each seamount. We used the identified environmental variables to predict the distribution of communities beyond the sampled areas, then described the spatial patterns and patch characteristics of the predicted community distributions. We found the environmental variables that best explained variations in community structure differed between the seamounts and at different spatial scales. These differences were reflected in the distribution models: communities on one seamount were predicted to form bands with depth, while on the other seamount communities varied mostly with broadscale aspect and the presence of small pinnacles. The number and size of community patches, inter-patch distances, and patch connectedness were found to differ both within and between seamounts. These types of analyses and results can be used to inform the spatial management of seamount ecosystems.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Fine Scale Assemblage Structure of Benthic Invertebrate Megafauna on the North Pacific Seamount Mokumanamana - Nicole B. Morgan; Savannah Goode; E. Brendan Roark; Amy R. Baco (Frontiers in Marine Science, 2019)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Organochlorine Pesticides in Squamate Reptiles from Southern Arizona, USA - Scott M. Weir; Marianne Dobrovolny; Chelsea Torres; Cassie Torres; Matt Goode; Thomas R. Rainwater; Christopher J. Salice; Todd A. Anderson (Bulletin of Environmental Contamination and Toxicology, 2013)

Genomics of the NF-κB signaling pathway: hypothesized role in ovarian cancer - Kristin L. White; David N. Rider; Kimberly R. Kalli; Keith L. Knutson; Gail P. Jarvik; Ellen L. Goode (Cancer Causes & Control, 2011)